SPARC promotes fibroblast proliferation, migration, and collagen production in keloids by inactivation of p53. Issue 1 (January 2023) - Shi, Shanshan; Li, Qiuchen; Liu, Yanxin; Zhang, Rui; Chen, Huaxia
Abstract: Background: Keloid, an aggressive fibroproliferative disease of the skin, is usually caused by infectious skin diseases, burns, and trauma. Objective: This study aimed to assess the effect of SPARC on the keloid pathogenesis. Methods: In normal skin and keloid scar tissues, changes in SPARC expression were analysed by qRT-PCR, western blotting, and immunohistochemistry. Keloid fibroblasts were isolated from human keloid tissue. GSEA was performed to investigate the signalling pathways related to SPARC. Cell Counting Kit-8, 5-Ethynyl-2′-deoxyuridine, transwell assay, and scratching assays were used to assess fibroblast proliferation and migration. Changes in α-SMA, fibronectin, collagen I, and collagen III levels were examined in fibroblasts by western blotting. Results: SPARC expression was upregulated in keloid scar tissues. In fibroblasts, cell proliferation, migration, collagen production, and extracellular matrix (ECM) synthesis were promoted by SPARC overexpression, whereas SPARC knockdown resulted a converse result. GSEA showed that SPARC regulates the p53 pathway. In keloid scar tissues, there was a negative correlation between SPARC and p53 expression. p53 expression was decreased by SPARC overexpression, whereas SPARC knockdown increased p53 expression. Furthermore, the effects of SPARC on the fibroblast phenotype were reversed by p53 overexpression. Conclusions: Fibroblast proliferation, migration, and ECM synthesis were promoted by SPARC overexpression, which was achieved by regulating the p53 pathway. Our findings provide new therapeutic targets for keloids. Highlights: SPARC expression is upregulated in keloid skin tissues. SPARC promotes the proliferation and migration of keloid fibroblasts. SPARC promotes the collagen production and ECM synthesis in fibroblasts. SPARC inhibits the activation of p53 signaling in fibroblasts.